2006
DOI: 10.1111/j.1462-5822.2005.00603.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori CagA transfection of gastric epithelial cells induces interleukin-8

Abstract: SummaryTo determine the effect of Helicobacter pylori CagA expression on interleukin-8 (IL-8) induction in AGS cells, cagA and five of its fragments from strains 147A and 147C that vary in the 3 ′ ′ ′ ′ repeat region were cloned into the eukaryotic expression plasmid pSP65SR α α α α . IL-8, but not RANTES or IL-I β β β β , levels were increased in AGS cells transfected with 147A-cagA and to a greater extent with 147C-cagA , compared with negative controls. The 5 ′ ′ ′ ′ b fragment from the two strains had simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 44 publications
6
95
0
Order By: Relevance
“…1A). Differences in the mobility of the CagA protein reflect the previously observed microheterogeneity in the cagA open reading frame (31,32). These results confirm that the CagA molecules we study bind to SHP2, as determined by tyrosine phosphorylation status.…”
Section: Role Of Caga Tyrosine Phosphorylation Status and Shp2supporting
confidence: 76%
See 2 more Smart Citations
“…1A). Differences in the mobility of the CagA protein reflect the previously observed microheterogeneity in the cagA open reading frame (31,32). These results confirm that the CagA molecules we study bind to SHP2, as determined by tyrosine phosphorylation status.…”
Section: Role Of Caga Tyrosine Phosphorylation Status and Shp2supporting
confidence: 76%
“…Bacteria, Cell Culture, and Co-incubation with H. pylori-A pair of naturally occurring isogenic cagA strains (147C, with a 3Ј tyrosine phosphorylation motif, and 147A, without the motif) isolated simultaneously from the same host have been described (31)(32)(33) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vector containing GFP without a CagA fragment was used as a control. Previous studies have demonstrated that the C-terminal CagA fragment exhibits CagA activity, including the induction of cell elongation and interleukin-8 secretion in AGS cells (14,18). This fragment, which contains the terminal third of the CagA protein, was observed to induce greater cell elongation than the complete CagA protein (18).…”
Section: Resultsmentioning
confidence: 99%
“…This CagA C-terminal fragment was amplified by polymerase chain reaction and cloned into the pAcGFP1-C3 vector (Clontech Laboratories, Inc., Mountainview, CA, USA) downstream to and in frame with green fluorescent protein (GFP). The primers used were as follows: CagA-DF, GGA TTG AGC TCA TGG GAA CAG GCG ATT TCA GTG GGG TAG and CagA-DR, CCG AGG TAC CTT AAG ATT TTT GGA AAC CAC CTT TTG TA (14). The CagA-DF and CagA-DR primers contained SacI and KpnI restriction sites (italicized above), respectively.…”
Section: Cloning and Mutagenesis Of The Caga C-terminal Regionmentioning
confidence: 99%